Synthesis and in vitro α-chymotrypsin inhibitory activity of 6-chlorobenzimidazole derivatives. Issue 16 (15th August 2016) - Siddiqui, Hina; Farooq, Rabia; Marasini, Bishnu P.; Malik, Rizwana; Syed, Naima; Moin, Syed Tarique; Atta-ur-Rahman,; Choudhary, M. Iqbal
Graphical abstract: Abstract: A library of benzimidazole derivatives1 –20 were synthesized, and studied for their α-chymotrypsin (α-CT) inhibitory activity in vitro. Kinetics and molecular docking studies were performed to identify the type of inhibition. Compound1 was found to be a good inhibitor of α-chymotrypsin enzyme (IC50  = 14.8 ± 0.1 μM, K i  = 16.4 μM), when compared with standard chymostatin (IC50  = 5.7 ± 0.13 μM). Compounds2 –8, 15, 17, and18 showed significant inhibitory activities. All the inhibitors were found to be competitive inhibitors, except compound17, which was a mixed type inhibitor. The substituents ( R ) in para and ortho positions of phenyl ring B, apparently played a key role in the inhibitory potential of the series. Compounds1 –20 were also studied for their cytotoxicity profile by using 3T3 mouse fibroblast cells and compounds3, 5, 6, 8, 12 –14, 16, 17, 19, and20 were found to be cytotoxic. Molecular docking was performed on the most active members of the series in comparison to the standard compound, chymostatin, to identify the most likely binding modes. The compounds reported here can serve as templates for further studies for new inhibitors of α-chymotrypsin and other chymotrypsin-like serine proteases enzymes.